IMPLEMENTATION AND PERFORMANCE ANALYSIS OF A COMPACT SOLAR STILL STANDALONE SYSTEM FOR SUSTAINABLE WATER POLLUTION (CAHIERS MAGELLANES-NS, 2024)
This study focuses on the design, implementation, and performance analysis of a compact solar still standalone system aimed at sustainable water purification. As freshwater scarcity intensifies globally, solar stills offer viable solution by harnessing solar energy for desalination and purification. The proposed system is designed to be compact, cost-effective, and easy to deploy, making it suitable for remote and off-grid areas. The implementation process involves construction of solar still with optimized dimensions to maximize solar absorption and condensation efficiency. Key features include high-transparency glass cover, black-coated basin to enhance heat absorption, and an effective sealing mechanism to minimize heat loss. System also incorporates condenser made of thermally conductive materials to expedite condensation process. Performance analysis was conducted under varying environmental conditions to assess system’s efficiency and reliability. Metrics such as water yield, solar intensity, ambient temperature, and humidity were meticulously recorded and analyzed. Results demonstrated that compact solar still could produce up to 6.7 liters of purified water per square meter per day under optimal conditions, with notable efficiency during peak solar hours. This research concludes that compact solar still standalone system is promising solution for sustainable water purification, particularly in areas with limited access to freshwater and electricity.